2022
DOI: 10.3390/v14010106
|View full text |Cite
|
Sign up to set email alerts
|

The Petasites hybridus CO2 Extract (Ze 339) Blocks SARS-CoV-2 Replication In Vitro

Abstract: The coronavirus disease 2019 (COVID-19), caused by a novel coronavirus (SARS-CoV-2), has spread worldwide, affecting over 250 million people and resulting in over five million deaths. Antivirals that are effective are still limited. The antiviral activities of the Petasites hybdridus CO2 extract Ze 339 were previously reported. Thus, to assess the anti-SARS-CoV-2 activity of Ze 339 as well as isopetasin and neopetasin as major active compounds, a CPE and plaque reduction assay in Vero E6 cells was used for vir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 74 publications
0
2
0
1
Order By: Relevance
“…The aqueous extract of the stem bark and leaf mixture of Bersama abyssinica (also known as Coviba dawa) demonstrated a 75% plaque reduction at 50 μg/mL, whilst the ethylacetate fraction of the leaves demonstrated a 50% inhibition (Zekeya et al, 2022). In a CPE and plaque reduction experiment in Vero E6 cells, Urda et al (2022) found that a lipophilic subcritical CO 2 extract made from Petasites hybridus leaves greatly reduced viral replication.…”
Section: Plants and Natural Products Anti‐sars‐cov‐2mentioning
confidence: 99%
“…The aqueous extract of the stem bark and leaf mixture of Bersama abyssinica (also known as Coviba dawa) demonstrated a 75% plaque reduction at 50 μg/mL, whilst the ethylacetate fraction of the leaves demonstrated a 50% inhibition (Zekeya et al, 2022). In a CPE and plaque reduction experiment in Vero E6 cells, Urda et al (2022) found that a lipophilic subcritical CO 2 extract made from Petasites hybridus leaves greatly reduced viral replication.…”
Section: Plants and Natural Products Anti‐sars‐cov‐2mentioning
confidence: 99%
“…Halk hekimliğinde solunum yolu rahatsızlıkları, sindirim sistemi hastalıkları ve baş ağrısının tedavisinde kullanıldığı beliritilmektedir (26). Bitkiden elde edilen ekstraktların ve bileşiklerin migren, alerjik rinnit, meme kanseri ve SARS-CoV-2 üzerinde etkili olduğu bilinmektedir (27)(28)(29)(30). Ayıca bitki antimikrobiyal ve antioksidan etki göstermektedir (31).…”
Section: Kabalak Otu (Petasites Hybridus)unclassified
“…The next section focuses on SARS-CoV-2 antivirals and treatments and includes two communications describing the antiviral activity of liposomal lactoferrin against HCoV-229E and SARS-CoV-2 pseudotyped viruses in vitro (70) and the safety and effectiveness of Molnupiravir against SARS-CoV-2 in hemodialyzed patients and kidney transplant recipients (71), and ten original research documents describing different aspects of antiviral research against SARS-CoV-2 in vitro or in validated animal models of viral infection (72)(73)(74)(75)(76)(77)(78)(79)(80)(81).…”
mentioning
confidence: 99%